Karakteristik dan Produktivitas Lahan Sawah Irigasi di Kecamatan Duampanua Kabupaten Pinrang - Rachmad Wunangkolu; Rismaneswati Rismaneswati; Christianto Lopulisa (Universitas Hasanuddin, 2019)
Land potential can be assessed from biophysical land suitability including soil characteristics, climate, and land management. This study aims to determine the potential of paddy fields in Duampanua Sub-District, Pinrang District for irrigated paddy field based on the land biophysical characteristics. The method was qualitative and quantitative approaches. Field surveys use purposive sampling method with 3 object observation. The land suitability class evaluation uses a simple limiting factor approach according to FAO (1976). To support the analysis of rice production data, 30 farmers were interviewed in 3 (three) observation units. The results showed the average rainfall of 2,780.2 mm/year with 9 wet months and 3 dry months categorized as type B2 (Oldeman). The results of soil samples analysis showed the characteristics of the soil with a silty clay texture, silty clay loam and clay; bulk density ranges from 1.36-1.66 g/cm3; cation exchange capacity ranges from 49.64 - 79.75 cmol/kg clay; soil pH ranges from 5.26-5.97; base saturation ranges from 36% - 46.4%; and C-organic ranges from 1.34% - 1.38%. The most dominant types of minerals are orthoclase, biotite, pyroxene, augite, opaque and clay with the symptoms of micropedological concretions and nodules. The land suitability class in the three land units for irrigated paddy rice is classified as S2nr (quite suitability in accordance with the limiting factors for nutrient retention including: base saturation, pH, and C-organic). The average productivity in land units I is 5.1 ton/ha, land unit II is 4.5 ton/ha, and in land units III 5.26 ton/ha.